Peran Teknologi Informasi dalam Meningkatkan Efisiensi Proses Akuntansi di Perusahaan Kecil dan Menengah - Filomena; Abdul; Gusti (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2025)
This research aims to analyze the role of information technology in improving the efficiency of accounting processes in small and medium enterprises (SMEs). In today's digital era, the use of information technology is an important factor in supporting business operations, including in financial recording, reporting, and analysis activities. The research method used is a descriptive qualitative approach with data collection through interviews, observations, and documentation studies on several SMEs that have implemented technology-based accounting systems. The results show that the application of information technology, such as accounting software and cloud-based systems, significantly helps speed up the accounting process, reduce recording errors, and improve the accuracy and transparency of financial statements. However, there are several challenges such as limited skilled human resources and system implementation costs. In conclusion, information technology has a crucial role in improving the efficiency of the accounting process in SMEs, although it requires the right strategy in its application so that the benefits can be felt optimally.